Peran Menajemen Pengelolaan Pendidikan Pada Gerakan Literasi di Sekolah (Kajian Terhadap SDN 50 Kecamatan Bengkalis, Kabupaten Bengkalis) - Sudarmi Sudarmi (STAIN Bengkalis, 2018)
Best Practice entitled the Effective Eductation Management to Achieve School Literacy Movement at SDN 50 Bengkalis. This study is School Action Research (PTS). It was conducted from January to March 2018 and it aimed to create a literate school Environment, in which the participation of all school residents is greatly to sucess of the school literacy movement program at SDN 50 Bengkalis.